Neural representation of sensorimotor features in language-motor areas during auditory and visual perception - Yuanyi Zheng; Jianfeng Zhang; Yang Yang; Min Xu (Communications Biology)
Abstract Speech processing involves a complex interplay between sensory and motor systems in the brain, essential for early language development. Recent studies have extended this sensory-motor interaction to visual word processing, emphasizing the connection between reading and handwriting during literacy acquisition. Here we show how language-motor areas encode motoric and sensory features of language stimuli during auditory and visual perception, using functional magnetic resonance imaging (fMRI) combined with representational similarity analysis. Chinese-speaking adults completed tasks involving the perception of spoken syllables and written characters, alongside syllable articulation and finger writing tasks to localize speech-motor and writing-motor areas. We found that both language-motor and sensory areas generally encode production-related motoric features across modalities, indicating cooperative interactions between motor and sensory systems. Notably, sensory encoding within sensorimotor areas was observed during auditory speech perception, but not in visual character perception. These findings underscore the dual encoding capacities of language-motor areas, revealing both shared and distinct neural representation patterns across modalities, which may be linked to innate sensory-motor mechanisms and modality-specific processing demands. Our results shed light on the sensorimotor integration mechanisms underlying language perception, highlighting the importance of a cross-modality perspective.